Dissemination of design literacy through the everyday environment: a study of design as driver in the Australian post office - Wong, Brendan (Curtin University, 2003)
Context: This study was founded on the notion that opportunities for individuals to improve their knowledge of and appreciation for design should be accessible to a broad population. If design is considered a driver in the development of environments that people encounter as part of their everyday activities, they may learn about design from those encounters. With a visual database of environments that include positive design examples, the population will benefit. Firstly, they have the capacity to use their informed encounters to contribute with some authority to discourse that shapes the future of their individual and collective surroundings. Secondly, they hold a greater expectation for design which can increase economic activity through design-related industry. Aim: The Australian post office (PostShop) was chosen as an example of an everyday environment that has the capacity to capture a large audience, due to an ever-increasing and proven catchment of the population-currently one in eighteen Australians will visit each day. To understand the role of design in the PostShop environment it is essential to understand the process through which the environment is developed, and those criteria that drive the final outcome. Therefore, the aim of this study is to investigate the extent to which the key development drivers of the PostShop influence the inclusion of design as a driver. Background: To enable this investigation to take place within an established context, a review of background literature was undertaken. This included themes supporting design literacy; the history of the PostShop built environment; brand; fitout and landlord guidelines for the built environment; global postal models; organisational behaviour; the development process; and the role of design in improving economic growth.Methodology: The qualitative approach was used during the research undertaken in this study. Semi-structured interviews were held with participants from Australia Post and other (external) organisations to capture data relating to the development process of the Postshop, and the role of design in that process. This data was categorised and coded according to themes that emerged from the interview data. This allowed the reduction of data for analysis and presentation. The presentation is primarily rich narrative descriptions and includes responses from interview participants. Key findings: The data uncovered thirty-three individual drivers that have contributed to the development of the postal environment over time. These drivers were presented to illustrate their changing importance over time, from early traditional post offices through to the current PostShop. Seventeen drivers were considered to be relevant today. These were distilled to four chief driver groups that influence the current PostShop. In rank order, these are : financial motivation: including minimisation of rental outgoings, capital fitout costs and business downtime during refurbishment; and queue operation organisational behaviour: including authority of internal opinion: and competition and personal imprimatur brand strategy: including the desire to be a modern retailer; national and tiered fitout standards; and measurement of the built environment as a brand medium external authority: including postal and other industry models; government pressure; and landlord guidelines.Conclusions: The aim of this study was to investigate the extent to which the key development drivers of the PostShop influence the inclusion of design as a driver. It was concluded that: all chief driver groups limit opportunities for design to contribute as a driver towards enhanced PostShop success. Despite being one of the leading international postal providers in terms of economic results, the chief drivers fail to embrace further potential for economic growth. The chief drivers also prevent the PostShop acting as an everyday environment that could successfully enhance the design literacy of the one million Australians that visit each day.